Composite Soil: Fiber Inclusion and Strength - Chegenizadeh, Amin; Nikraz, Hamid (Trans Tech Publications Inc, 2011)
Reinforced soil has been among the most effective soil modification materials. Its use has been expanded rapidly into civil engineering, geotechnical engineering and pavement engineering. Reinforcing subgarde in pavement systems has always been an issue. This study focuses on effect of fiber inclusion on the strength of subgrade material. Plastic fiber was used for this investigation. Fiber contents and aspect ratio have been changed during these tests. The fiber percentage varied from 0 % (for unreinforced samples) to 2%. Clay was used as sub grade material. Unconfined compression tests were carried out to investigate behaviour of the composite under different condition. The fiber length and fiber content found to play important rule on the strength of composite. Furthermore it was observed that ductility of sample increased by fiber inclusion.